2015
DOI: 10.1016/j.apenergy.2015.08.095
|View full text |Cite
|
Sign up to set email alerts
|

Changing urban forms and carbon dioxide emissions in China: A case study of 30 provincial capital cities

Abstract: h i g h l i g h t sThe relationship between urban form and CO 2 emissions is investigated. A panel data model is used, taking the period 1990-2010. The growth of urban areas correlates positively with CO 2 emissions. Increases in urban continuity has an inhibitory effect on CO 2 emissions. Increased urban shape complexity exhibits a positive influence in relation to CO 2 emissions. a r t i c l e i n f o a b s t r a c tUrban form is increasingly being recognised by scientists for the potential role it might pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(108 citation statements)
references
References 59 publications
(83 reference statements)
2
77
0
Order By: Relevance
“…As indicated by Figure 3, both the absolute amount and density of infrastructure's material stocks have reached a relatively high level in the eastern region, comparing to those in the central and western regions. It has also been confirmed by our panel analysis that the increase of infrastructure stock density will reduce CO 2 emissions in the eastern region, which is consistent with the findings in many existing studies that a spatially compact urban form usually consumes less energy [9,37,38]. Moreover, as shown in Figure 4, in some highly urbanized areas such as Yangtze River Delta (YRD), Pearl River Delta (PRD), and Beijing-Tianjin-Hebei (BTH), their economic development has reached a high level and thus had a large amount of infrastructure stocks and high stock density.…”
Section: Discussion and Policy Implicationssupporting
confidence: 77%
See 1 more Smart Citation
“…As indicated by Figure 3, both the absolute amount and density of infrastructure's material stocks have reached a relatively high level in the eastern region, comparing to those in the central and western regions. It has also been confirmed by our panel analysis that the increase of infrastructure stock density will reduce CO 2 emissions in the eastern region, which is consistent with the findings in many existing studies that a spatially compact urban form usually consumes less energy [9,37,38]. Moreover, as shown in Figure 4, in some highly urbanized areas such as Yangtze River Delta (YRD), Pearl River Delta (PRD), and Beijing-Tianjin-Hebei (BTH), their economic development has reached a high level and thus had a large amount of infrastructure stocks and high stock density.…”
Section: Discussion and Policy Implicationssupporting
confidence: 77%
“…For example, Poumanyvong and Kaneko [7] suggested that the impact of urbanization on CO 2 emissions was positive for all income groups, while Sharma et al [8] held the opposite opinion that urbanization has a negative and statistically significant impact on CO 2 emissions for the global panel. Fang et al [9] selected a series of urban form indicators and found that increased urban continuity will led to reductions in CO 2 emissions and that, conversely, increased urban shape complexity and exerted a positive influence in relation to CO 2 emissions. Yang et al [10] found that socio-economic development and increased income were the primary driving factors for the growth of per capita CO 2 emissions from transportation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, decelerating the economic growth process could be the most effective method of reducing energy consumption and mitigating global climate change. However, rapid economic growth and urbanization are currently the main goals of the Chinese government [50]. Therefore, the government faces the arduous challenge of continuously balancing increases in urban energy consumption and rapid economic growth with meeting environmental goals [25].…”
Section: Development Recommendationsmentioning
confidence: 99%
“…This is questionable due to its multiple facets (e.g., urban area, urban density, residential dwelling spatial structure) across countries and geographical regions. In addition, many recent empirical studies have found that some urban form variables (e.g., urban area, residential density, housing sizes and types, urban structure) can have significant impacts on environment (i.e., carbon emission, energy use) (Boyko and Cooper, 2011;Fang et al, 2015;Lee and Lee, 2014;Norman et al, 2006;Perkins et al, 2009;Reingewertz, 2012 ;Yang et al, 2015;Yin et al, 2015). Therefore, further studies with careful considerations of the different urban forms become imperative.…”
Section: Introductionmentioning
confidence: 99%